Blood and Tissue Silver Levels Following Application of Silver-Based Dressings to Sulfur Mustard Chemical Burns. Issue 5 (September 2017) - Barillo, David J.; Croutch, Claire R.; Reid, Frances; Culley, Tara; Sosna, William; Roseman, Julie
Abstract : Silver-based dressings are commonly used in burn care. Silver sulfadiazine use is associated with elevated blood, urine, and tissue levels of silver ion. We examined wound and tissue levels of silver ion in a two-species model of sulfur mustard chemical burn injury treated with two different silver-based dressings. Superficial dermal and moderate thickness dermal chemical burns were induced in 16 hairless guinea pigs and in 16 Gottingen minipigs by exposure to sulfur mustard vapor. After debridement, silver-nylon burn dressings or silver-calcium alginate dressings were applied and changed every 7 days until wound healing or a maximum of 60 days post exposure. At autopsy, liver, spleen, and wound samples were harvested. Silver ion was measured using inductively coupled plasma-mass spectrography with a lower level of detection of 0.02 parts per billion. Negligible silver ion levels were found in the liver (mean < 0.003 μg/g of tissue) and spleen (mean < 0.05 μg/g) of all 32 animals. Wound biopsies showed silver ion levels ranging from 0.07 to 19.5 μg/g of tissue. Wound levels were higher in minipigs than in hairless guinea pigs and were higher in animals treated with silver-nylon burn wound dressings than with silver-calcium alginate dressings. Silver ion could be detected in some wounds 40 days after dressings were removed. In a chemical burn model, application of silver-nylon or silver-calcium alginate dressings is associated with elevated wound levels but negligible tissue levels of silver ion.